Comparative analysis of lactaptin activity when produced in bacterial or eukaryotic expression systems - O. A. Koval; O. Y. Volkova; A. A. Gorchakov; S. V. Kulemzin; A. V. Tkachenko; A. A. Nushtaeva; E. V. Kuligina; V. A. Richter; A. V. Taranin (Вавиловский журнал генетики и селекции)
Despite the multitude of anticancer cytostatic drugs available to oncologists today, most of such drugs have serious side effects that may preclude their use in some groups of patients. Hence, selective induction of apoptosis in cancer but not normal cells remains an attractive goal of molecular medicine. Lactaptin, a proteolytic fragment of the human milk kappa-casein, has been previously identified as a protein displaying potent killing of cancer cells in vitro. Its recombinant analog (RL2) produced in E. coli has been shown to delay solid tumor growth in vivo. Given that lactaptin is of human origin and is not immunogenic, it can be administered to patients multiple times without running the risk of immune response that could dampen the therapy efficacy. In the present study, we demonstrate that the combination of RL2 and cyclophosphamide treatments has an additive therapeutic effect against hepatoma tumor in immunocompetent mice. We asked whether production of lactaptin in human rather than bacterial cells would result in a protein with increased cytotoxic activity. Using lentiviral vector pCDH as a backbone, two constructs, pEL1 and pEL2, encoding secreted forms of lactaptin that differ in their signal sequences were created. Lactaptin expression in human cell lines was confirmed using Western-blot analysis, whereas ELISA was used for quantification of secreted lactaptin. Next, we measured the cytotoxic effects of the media conditioned by pEL1-transfected HEK293T cells, as assayed against the panel of three human cancer cell lines: MDA-MB-231 (adenocarcinoma), PC3 (prostate cancer), and T98G (glioblastoma). We show that EL1-derived lactaptin is at least 100-fold more cytotoxic than RL2. Taken together, our results provide an opportunity for developing armored immune cells as an “off-the-shelf” platform for targeted delivery of lactaptin to cancer cells.